Extensive spontaneous cerebral haemorrhage after Russell’s viper bite - Chattopadhyay, Mounam (BMJ Case Rep, 2020)
A 30-year-old man presented with altered sensorium following Russell’s viper bite, which was found to be secondary to intracranial hemorrhage secondary to venom-induced consumptive coagulopathy. He was managed conservatively with blood component transfusion and antivenom injection, and successfully discharged.